Azuperylene: The Nonalternant Isomer of Perylene - Liu, Shengpei; Díaz-Fernández, Marcos; Zhang, Menglin; Huang, Fei; Chen, Yong; Yang, Yudong; Marín-Beloqui, José Manuel; Lan, Jingbo; You, Jingsong; Casado-Cordón, Juan; Zhang, Cheng (Wiley, 2025)
The isoelectronic isomer of perylene, hereafter called as azuperylene, has been prepared. Electronic structure analysis reveals that the new isomer can be described as a union of two antiparallel azulenes in which the azulene-type aromatic character of the starting azulene is partially retained. Four 2,8-dialkoxy (i.e., ethoxy, n-butoxy, n-hexyloxy, and n-octyloxy) functionalized derivatives of the new isomer core have been prepared. The solid-state structures of the new compounds have been resolved showing exceptional herringbone π–π stacking ideal for charge transport. Organic field-effect transistors on sublimated substrates display an excellent hole transport mobility up to 1.03 cm2 V−1 s−1 that largely surpasses that of perylene and reveals the great potential for charge transport of this new class of nonbenzenoid compounds.
Keywords: Química física; Electrónica órganica; Azulene; Electronic isomers; organic semiconductors; polycyclic aromatic hydrocarbons; Perylene